2019
DOI: 10.1002/ejoc.201900952
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Hydrogen Atom Transfer (HAT) Catalysis for Rapid and Selective Reductive Photoredox Transformations in Continuous Flow

Abstract: The reductive transformation of aryl halides and carbonyl compounds is a key step in many photoredox transformations. By combining a highly reducing organic photocatalyst with a thiol hydrogen atom transfer (HAT) catalyst, we showcase rapid and highly selective reactions of these synthetically important starting materials in continuous flow. The fast reduction of aryl iodides, bromides and chlorides has been demonstrated with residence times in some cases below one minute. Selectivity between mono‐ and di‐deha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
(29 reference statements)
2
15
0
Order By: Relevance
“…The optical properties of the polymers were studied via UV/vis spectroscopy in water as well as organic solvent (i.e., acetonitrile; see Figure S5 in the Supporting Information). The UV/Vis spectra show in both solvents the typical absorption bands of the incorporated PTH catalyst with maxima at around 258 and 320 nm, indicating the successful incorporation of the photocatalyst within the polymer scaffold (in accordance with NMR spectroscopy, see Figures S6–S8 in the Supporting Information).…”
Section: Resultssupporting
confidence: 76%
“…The optical properties of the polymers were studied via UV/vis spectroscopy in water as well as organic solvent (i.e., acetonitrile; see Figure S5 in the Supporting Information). The UV/Vis spectra show in both solvents the typical absorption bands of the incorporated PTH catalyst with maxima at around 258 and 320 nm, indicating the successful incorporation of the photocatalyst within the polymer scaffold (in accordance with NMR spectroscopy, see Figures S6–S8 in the Supporting Information).…”
Section: Resultssupporting
confidence: 76%
“…In the literature, there are a number of examples on light-induced hydrodehalogenation of aryl halides. 14 , 34 Here, by simply removing B 2 Pin 2 from the reaction conditions, the reductive dehalogenation of aryl halides occurred smoothly with good to excellent yields ( Table 8 ). A panel of functional groups such as ester, ketone, cyano, amide and alcohol were tolerated.…”
Section: Resultsmentioning
confidence: 96%
“…Finally, the optical properties of the nanoparticles were studied with UV/Vis spectroscopy with water as solvent ( Figure S10 in the Supplementary Information ). It was previously reported that the PTH absorption maxima are located around 258 and 320 nm [ 43 ], whereas ACR absorption maxima occur at 360 and 520 nm [ 16 ]. Both the polymer bound ACR and PTH moiety show absorption bands identical to those reported in the literature for the free catalysts.…”
Section: Methodology and Resultsmentioning
confidence: 99%